Endovascular Histologic Effects of Ultrathin Gold- or Vitronectin-Coated Platinum Aneurysm Coils in a Rodent Arterial Occlusion Model: A Preliminary Investigation - Whitlow, C.T.; Geer, C.P.; Mattern, C.W.T.; Mussat-Whitlow, B.J.; Yazdani, S.K.; Berry, J.L.; Lalli, J.H.; Claus, R.O.; Challa, V.R.; Morris, P.P. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Novel stratagems to improve the efficacy of platinum coils in occluding cerebral aneurysms have primarily involved coating coils with materials thought likely to provoke more desirable histologic reactions. No investigations to date, however, have evaluated the utility of gold or vitronectin coatings, despite known endovascular histologic effects of these agents, which may be favorable for treating cerebral aneurysms. This study was conducted to evaluate the degree of endovascular histologic change associated with ultrathin gold- or vitronectin-coated platinum coils. It was hypothesized that such coatings would increase intra-aneurysmal intimal hyperplasia and the degree of luminal occlusion compared with standard platinum coils.MATERIALS AND METHODS: The ligated carotid artery rat model was used to study 4 different aneurysm coil conditions: no coil (sham-surgery controls), uncoated platinum coil, and gold- or vitronectin-coated platinum coil. Two weeks postimplantation, the aneurysms were harvested and stained with hematoxylin-eosin. Slides were evaluated for the degree of neointimal response by a pathologist blinded to treatment. Additional quantitative evaluation was performed blindly by using the ratio of intimal-to-luminal cross-sectional area.RESULTS: A gold- or vitronectin-coated platinum aneurysm coil produced a statistically significant increase in neointimal response compared with a sham (no coil). Arterial segments treated with gold-coated platinum coils also demonstrated a statistically significant 100% increase in neointimal response compared with those treated with bare platinum coils.CONCLUSIONS: In concordance with our hypothesis, ultrathin coatings of gold provoked a neointimal response and degree of luminal occlusion greater than that of plain platinum aneurysm coils in a rat arterial occlusion model.